Spatiotemporal characteristics of P-selectin-induced β2 integrin activation of human neutrophils under flow - Sun, Xiaoxi; Huang, Bing; Pan, Yuping; Fang, Jinhua; Wang, Hefeng; Ji, Yanru; Ling, Yingchen; Guo, Pei; Lin, Jiangguo; Li, Quhuan; Fang, Ying; Wu, Jianhua (Frontiers in Immunology, 2022)
Activation of integrins is crucial for recruitment of flowing leukocytes to inflammatory or injured vascular sites, but their spatiotemporal characteristics are incompletely understood. We discovered that β2-integrin activation over the entire surface of neutrophils on immobilized P-selectin occurred via mitogen-activated protein kinase (MAPK) or non-MAPK signaling with a minute-level timescale in a force-dependent manner. In flow, MAPK signaling required intracellular Ca2+ release to activate integrin within 2 min. Integrin activation via non-MAPK signaling occurred first locally in the vicinity of ligated P-selectin glycoprotein ligand-1 (PSGL-1) within sub-seconds, and then over the entire cell surface within 1 min in an extracellular Ca2+ influx-dependent manner. The transition from a local (but rapid) to global (but slow) activation mode was triggered by ligating the freshly activated integrin. Lipid rafts, moesin, actin, and talin were involved in non-MAPK signaling. Fluid loads had a slight effect on local integrin activation with a second-level timescale, but served as enhancers of global integrin activation.